Teaching-learning process through virtual mode during the pandemic time: Systematic literature review and gap analysis - Ajay Kumar Singh; Mukesh Kumar Meena (Universidad de Deusto, 2022)
PURPOSE: Due to the COVID-19 pandemic, the Higher Education Institutes (HEIs) was closed temporarily. During this historical lockdown, the face-to-face mode classroom was temporarily got replaced by a virtual classroom. The objective of this study was to analyze the impact of nationwide lockdown on the benefits of the virtual classroom for the teaching-learning process for teachers and students due to change in the teaching-learning process in higher education during the COVID-19 pandemic.     DESIGN: A total of 893 responses have been used for this study. We have collected data through a structured questionnaire on a Likert scale from 305 teachers and 588 students of Higher Education Institutes (HEIs) from all India levels. Descriptive and frequency statistics, t-test was used in SPSS software to analyze the data collected through the primary source.     FINDINGS: The mean difference between expected benefits from the virtual classroom and actual benefits from the classroom is positive for students as well as faculty members. That indicates the overall mean of expected benefits is higher than the overall mean of actual benefits, and that difference value is 0.250055, with a Sig. (2-tailed) value of 0.036 which is less than 0.05 for teachers and 0.3872827, with a Sig. (2-tailed) value of 0.000 which is less than 0.05 for students. That indicates the significant difference between means of actual benefits and expected. The mean value of the expected benefit is higher than the mean value of actual benefits for 11 pairs and 08 pairs in the case of teachers and students respectively.     DISCUSSION: Technical barriers are the reasons for not being able to attend the expected benefits from virtual classrooms in full capacity by students as well as by faculty members. Poor digital skills of teachers and students, lack of electricity facilities, less availability and accessibility of internet, connection issues, inadequate facilities, training, funding, and unacceptability of technology, etc. were the barriers to online education at the time of closure of colleges due to COVID-19 pandemic Onyema et al. (2020). Students can also have a casual attitude, less attendance, feeling of isolation and less interaction can lead to mental distress, spending more time in front of a computer could be hazardous for health too Surkhali and Garbuja (2020). Higher Education Institutes (HEIs) faculty members, as well as students, were not able to perceive actual benefits in full in comparison to expected benefits due to the presence of challenges in the virtual classroom as moderators. The higher education authorities, colleges/institutes/universities need to fix the above issues to enhance the quality of the teaching-learning process. The higher education authorities, institutes/colleges/universities must work together to resolve the issues and challenges of virtual classrooms to improve their effectiveness of the virtual classroom. Higher Education Institutes (HEIs) may provide technical support, and training to the faculty members as well as students for a better experience in the virtual classroom. Students who are lacking technical infrastructures such as computers/laptops and internet connectivity may be provided by Higher Education Institutes (HEIs) with financial and technical support to these students. Received: 18 November 2021 Accepted: 25 October 2022